2013
DOI: 10.1590/s2317-64312013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Uso de aparelho de amplificação sonora individual por idosos: estudo SABE - saúde, bem- estar e envelhecimento

Abstract: Purpose: Describe hearing aid use by the elderly population in the city of São Paulo and identify associated factors. Methods: A cross-sectional, descriptive, quantitative study integrated with the SABE (health, wellbeing and aging) project developed in 2006. A total of 1.115 individuals aged 65 or over were interviewed. Sample selection occurred in two stages, with replacement and probabilities proportional to the population to complement those aged 75 or over. Structured questionnaires and validated instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
2
7
0
3
Order By: Relevance
“…These findings agree with previous studies, 11,17,20 which reported lower thresholds of hearing, especially at high frequencies, for men. Factors such as high blood pressure, smoking and exposure to noise contributes to the worsening of hearing with age.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings agree with previous studies, 11,17,20 which reported lower thresholds of hearing, especially at high frequencies, for men. Factors such as high blood pressure, smoking and exposure to noise contributes to the worsening of hearing with age.…”
Section: Discussionsupporting
confidence: 94%
“…Due to sensory deprivation, the individual becomes unable to communicate properly with others, causing frustration and leading to a deterioration in quality of life. [10][11][12] The psychological and social damage (participation restrictions) arising from hearing loss is described as a handicap. 13,14 The evaluation of the impact of hearing loss on emotional and social aspects can be accomplished through the application of self-assessment questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…In a research of Cruz et al [30] performed with the elderly, 89.9% of the participants who self-referred hearing loss have not made use of a hearing aid and 10.1% ( n  = 45) have used it. When asked why they have not used the hearing aid, 8.6% said that although indicated, they had not got used to it and 8.0% had not acquired it because of financial problems.…”
Section: Discussionmentioning
confidence: 99%
“…Outro estudo 29 demonstra que a reabilitação auditiva propicia otimização de medidas cognitivas globais. O desenvolvimento da habilidade de atenção auditiva contribui para a diminuição do isolamento social e da dificuldade comunicativa e, portanto, para a melhora da qualidade de vida.…”
Section: ▄ Discussãounclassified